Beautiful ugly - Feeney, Alice (Flatiron Books, 2025)
"Author Grady Green is having the worst best day of his life. He calls his wife, Abby, to share some exciting news as she is driving home. He hears Abby slam on the brakes when she sees something in the road ahead. Over Grady's protests, Abby gets out of the car. When he eventually finds her car by the cliff edge, the headlights are on, the driver's door is open, her phone is still there... but his wife has disappeared. A year later, Grady is still overcome with grief and desperate to know what happened to Abby. He can't sleep, and he can't write, so he travels to a tiny, remote Scottish island to try and get his life back on track. And then he sees the impossible: a woman who looks exactly like his missing wife"--Inside jacket flap.